Perilaku Konsumen dalam Pemilihan Online Shop Instagram - Sukwadi, Ronald (Metris: Jurnal Sains dan Teknologi, 2016)
The primary purpose of this paper is to investigate the determinants of consumer purchase intention in online shop Instagram. 200 respondents were participated in this research. Data was collected using a survey method and analyzed using structural equation model AMOS 24. Result of natural experiment indicates that only satisfied customers will have intention to buy online products through Instagram.